Global energy market: development trends and relationships between its individual sectors - Stepurina, Svitlana; Huz, Ostap; Mehyar, Samer (IOSI, Center for Tech and Media Research, 2024)
The energy market is one of the key factors in the functioning of various business entities and economic development in general. Here it is important to take into account the conditions for the formation of such a market, the influence of various factors on its dynamics and trends in its development. For these purposes, it is advisable to consider data from the corresponding segment of the stock market on which securities of various energy market companies are traded. The dynamics of quotes for such securities helps to understand the obvious and hidden trends in the functioning of such a market. Based on this, the work examines quotes for the classical components of individual segments of the energy market. Among these components, prices for oil, gas, gasoline and fuel oil are highlighted. The work presents graphs for different data and their individual statistical characteristics. The dynamics of the relationship between individual segments of the energy market are also considered. The research results are confirmed by individual graphs and estimates, which also makes it possible to understand the overall progress of the study.
Keywords: development; interrelation; oil; gas; gasoline; fuel oil; energy market; statistical analysis; stock indices